Self-Regulated and Students Independent Learning Using Social-Media at Papua University - Suardi, Sahid; Riana , Murianty; Tifany, Gerda K. (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This research investigates the effectiveness of social media platforms to support students in independent learning to develop Self-Regulated Learning (SRL) skills. Social media platforms can be effective tools to support independent learning and the development of Self-Regulated Learning skills when used intentionally and strategically. They provide avenues for collaboration, resource access, goal setting, and reflection, all of which contribute to SRL. However, educators and students must be aware of potential distractions and ensure that social media use is guided by clear learning objectives and self-management strategies. The implementation of this research used a mixed method of quantitative and qualitative. A total of 37 students were sampled in this research, consisting of the Classes of 2023 and 2024. The data taken shows that many students use social media platforms in their independent learning. In independent learning, some social media platforms are widely used by students, such as YouTube, TikTok, and Instagram. With social media, students can search for material or further information related to learning. In practicing English learning. Students can know their knowledge using social media platforms. The other platforms that students use to practice their English are: Duolingo, Busu, and Cake.